PENGARUH KESADARAN PERPAJAKAN, SUNSET POLICY, SANKSI PAJAK DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada Kantor Pelayanan Pajak Pratama Ambon) - Tirza Oktovianti Lenggono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2018)
This study aims to determine the Effect of Tax Awareness, Sunset Policy,Tax Sanctions and Tax Amnesty Against Taxpayer Compliance. Population inthis research is Waji Personal Tax registered in KPP Pratama Ambon.Sampling was done by simple random sampling method. The data in thisstudy were obtained from the questionnaire (primary) with a sample of 100respondents. This study uses data quality analysis and classical assumptions andhypothesis testing.Result of research proves that, awareness of taxation have positive andsignificant effect to taxpayer compliance of individual that is shown with value oft count equal to 2,036 and significant value equal to 0,044, tax sanction havepositive and significant effect to taxpayer compliance of individual tax which isindicated by t value equal to 3,032 and the significant value of 0.003 and taxamnesty have a positive and significant effect on the taxpayer compliance of theindividual indicated by the value of t arithmetic of 2531 and the significant valueof 0.013. While sunset policy does not affect the taxpayer compliance ofindividuals who are shown with the value of t arithmetic of 0.971 and significantvalue of 0.334.